1997
DOI: 10.1108/09578239710161786
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of women principals’ leadership and teachers’ work attitudes

Abstract: Background of the studyThe importance of leadership has been strongly emphasized in the literature of school effectiveness and educational reforms (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In this regard, my proposition of a holistic definition of educational leadership is based on the process view of leadership and I surmise that effective leadership should encompass both the taskoriented as well as the relationship-oriented behavioural elements, as has been suggested by theorists including Shum and Cheng (1997), Gardner and Laskin (2011) and Northouse (2010Northouse ( , 2013. Thus, for this study, I define 'educational leadership' as 'a process whereby the school leader directly or indirectly influences the thoughts, behaviour and actions of all members associated with the educational institution, in order to improve the overall student performance and the quality of teaching and learning within the institution.…”
Section: )mentioning
confidence: 89%
See 1 more Smart Citation
“…In this regard, my proposition of a holistic definition of educational leadership is based on the process view of leadership and I surmise that effective leadership should encompass both the taskoriented as well as the relationship-oriented behavioural elements, as has been suggested by theorists including Shum and Cheng (1997), Gardner and Laskin (2011) and Northouse (2010Northouse ( , 2013. Thus, for this study, I define 'educational leadership' as 'a process whereby the school leader directly or indirectly influences the thoughts, behaviour and actions of all members associated with the educational institution, in order to improve the overall student performance and the quality of teaching and learning within the institution.…”
Section: )mentioning
confidence: 89%
“…However, the task-orientation aspect of educational leadership cannot be ignored either, as Shum and Cheng (1997) emphasize upon the distribution of educational and instructional knowledge to enhance the quality and impact of teaching, as an important aspect of educational leadership.…”
Section: Defining 'Educational' Leadershipmentioning
confidence: 99%
“…They do this by using democracy principles to make decisions and decide how to carry them out. Shum & Cheng (1997) of management and organization with regard to leadership have repeatedly shown that the style of leadership is a crucial factor in the organization's success and efficacy; which impacts either the beneficial or detrimental the process of organization and framework, trends in social interaction, members' opinions, views, and work behaviours. To achieve their goals and offer instructors job satisfaction, schools need successful leadership styles.…”
Section: Background Of Studymentioning
confidence: 99%
“…Furthermore, in Asia, other instruments for measuring self-efficacy have been developed by researchers. Shum and Cheng (1997) measured the self-efficacy of femaleleader teachers, Yeung and Watkins (2000) measured personal self-efficacy, and Kennedy and Hui (2006) developed the Chinese version of Teachers' Sense of Efficacy Scale (TSE).…”
Section: Self-efficacy Instrumentsmentioning
confidence: 99%